Copolyesters of 2,4-FDCA with improved crystallization control
Patent Information
- Application Number
- JP2023545943
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-29
- Filing Date
- 2022-01-27
- Publication Date
- 2025-01-30
AI Technical Summary
Existing PET compositions face challenges in maintaining crystallinity and barrier properties over time due to physical degradation, leading to increased haze and reduced mechanical performance, which affects the shelf life and logistics of packaged products, and the use of comonomers like isophthalic acid is costly and unsustainable.
Incorporation of 2,4-furandicarboxylic acid (2,4-FDCA) as a comonomer in PET formulations, combined with terephthalic acid and biobased monoethylene glycol, to create a copolyester with controlled crystallization rates and enhanced gas barrier properties, utilizing renewable carbon sources to reduce production costs.
The 2,4-FDCA copolyester exhibits improved crystallization control, higher biobased content, and superior gas barrier properties, enhancing the shelf life and performance of PET articles while reducing dependence on fossil feedstocks and operational costs.
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This PCT application claims priority to U.S. Provisional Patent Application No. 63 / 143,648, filed January 29, 2021, the disclosure of which is incorporated herein by reference in its entirety. [Background technology]
[0002] background The present invention relates generally to inventive terephthalate copolymers, and more particularly to poly(ethylene terephthalate) copolymers.
[0003] Poly(ethylene terephthalate), more commonly referred to as PET, is one of the most relevant commodity polymers on the market thanks to its diverse end uses, from polyester textile fibers to carbonated soft drink (CSD) bottles. PET is obtained by the polycondensation reaction between ethylene glycol and either terephthalic acid (TPA) or dimethyl terephthalate (DMT), resulting in a linear condensation polymer.
[0004] A typical reaction between these units consists of an initial condensation step followed by solid-state polymerization. These steps produce PET grades of different molecular weights, which are traditionally reported as intrinsic viscosity (IV) values. Depending on the IV, the resulting PET can be used in fiber applications (IV<0.65) or as a resin (IV=0.65-1.2).
[0005] PET resin is of major importance in the industry due to its use in bottles, where PET with IV>0.65 is blow moulded to produce bottles that can be used as containers for water, CSD, spirits, dairy products etc. This processing method is not only responsible for producing moulded articles but also for modifying the properties of PET by stretching the polymer chains, which become oriented under the action of strain induced during deformation.
[0006] Nonetheless, this strain is relieved over time by a mechanism called physical aging, which ultimately increases the crystallinity of post-processed PET resin articles that have undergone post-processing, including but not limited to blow molding. As a result, PET articles tend to gradually increase in haze and decrease in barrier and mechanical properties over time, compromising the shelf life of bottled products. This has significant implications for logistics, limiting storage and transportation times and leading to increased plastic consumption.
[0007] To overcome this challenge, manufacturers have typically added small amounts of comonomers to polymer formulations to introduce chain defects that slow the crystallization rate. Isophthalic acid, the meta-isomer of terephthalic acid, has traditionally been used in amounts of 1-3 mole percent relative to the diacid content of bottle-grade resins to extend the shelf life of these products.
[0008] Examples of the use of 2,5-FDCA in PET comonomers for crystallization are found in the art. For example, US 2018 / 0355100 A1 teaches the utilization of biomonoethylene glycol (bioMEG) in bioPET in combination with biosourced 2,5-furandicarboxylic acid and its esters for specific control of the crystallization rate of the resulting bioPET. Similarly, WO 2018089600 A1 teaches that 2,5-FDCA may be used as a crystallization control comonomer in PET compositions made with bioMEG. However, to date, despite their sustainable attractiveness and proven performance, none of these routes to produce 2,5-FDCA are mature enough to be commercialized in the near future. One of the main barriers to using 2,5-FDCA rather than isophthalic acid in PET compositions is related to the high production costs of the furan derivative, increasing the price of the resulting resins, compositions, and resulting articles. The addition of comonomers in PET for crystallization control is typically an act that increases operating costs, given the high price of isophthalic acid and other similar molecules compared to TPA and monoethylene glycol. Therefore, there is a cost barrier for any molecule expected to act as a competitive crystallization rate modifier, limiting the number of industrially available candidates. Compared to isophthalic and terephthalic acids, the approximate production cost per ton of furan derivatives is double, thus undermining the technical and sustainable potential of this platform.
[0009] Thus, there is a need for improved copolyesters with improved crystallization control and increased biobased content, which would be desirable in part to reduce the reliance of the polyester chain on fossil feedstocks and thus reduce sensitivity to price fluctuations and therefore margins relative to oil prices. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] US Patent No. 2018 / 0355100 A1 [Patent Document 2] International Publication No. 2018089600 A1 Summary of the Invention
[0011] overview The present disclosure provides a copolyester comprising a dicarboxylic acid component A comprising terephthalic acid residues or ester-forming derivatives thereof or mixtures thereof and 2,4-furandicarboxylic acid residues or ester-forming derivatives thereof or mixtures thereof, and a diol component B comprising an alkanediol residue having 2 to 22 carbon atoms, wherein the dicarboxylic acid component A has a total molar content and the 2,4-furandicarboxylic acid residues or ester-forming derivatives thereof are present in an amount of 0.1 to 10 mol % relative to the total molar content of the dicarboxylic acid component A. In some embodiments, the copolyester has a slower crystallization rate compared to a comparable copolyester comprising isophthalic acid instead of 2,4-furandicarboxylic acid. In some embodiments, the copolyester has at least 10% higher gas barrier properties against CO2 and O2 as measured by ASTM D1927-20 compared to a comparable copolyester comprising isophthalic acid instead of 2,4-furandicarboxylic acid. In some embodiments, the copolyester has at least 10% higher gas barrier properties against CO2 and O2 as measured by ASTM D6866 compared to a comparable copolyester comprising isophthalic acid instead of 2,4-furandicarboxylic acid. 12 For C 14 C. In some embodiments, the copolyesters have an intrinsic viscosity (IV) of 0.5 dL / g to 1.2 dL / g, measured at 30° C. in a 0.5 wt % solution of 60 / 40 phenol / 1,1,2,2-tetrachloroethane according to ASTM D4603-96.
[0012] In some embodiments, dicarboxylic acid component A has a total molar content and the 2,4-furandicarboxylic acid residues or ester forming derivatives thereof are present in an amount of 0.5 to 5 mol %, such as 1 to 3 mol %, based on the total molar content of dicarboxylic acid component A. In some embodiments, dicarboxylic acid component A has a total molar content and the terephthalic acid residues are present in an amount of 96.5 mol % to about 99.9 mol %, based on the total molar content of dicarboxylic acid component A.
[0013] In some embodiments, the alkanediol residue is a branched or straight chain alkanediol having 2 to 12 carbon atoms, e.g., 4 to 6 carbon atoms, while in other embodiments, the alkanediol residue is a cycloalkanediol having 5 to 10 carbon atoms. The alkanediol residue may include monoethylene glycol residues, propylene glycol residues, and / or butylene glycol residues. In some embodiments, the diol component B includes two or more of monoethylene glycol residues, propylene glycol residues, and butylene glycol residues. In some embodiments, the alkanediol residue is of bio-based origin.
[0014] In some embodiments, diol component B has a total molar content and monoethylene glycol is present in an amount of 92.5 mol % or more, based on the total molar content of diol component B. In some embodiments, diol component B has a total molar content and monoethylene glycol is present in an amount of 95 mol % or more, based on the total molar content of diol component B, e.g., monoethylene glycol may be present in an amount of 99 mol % or more, based on the total molar content of diol component B, or diol component B may consist essentially of monoethylene glycol.
[0015] Diol component B may further comprise additional hydroxyl-containing residues. In some embodiments, diol component B has a total molar content where the additional hydroxyl-containing residues are present in an amount of about 7.5 mol % or less of the total molar content of diol component B. In some embodiments, the additional hydroxyl-containing residues are present in an amount of about 1 mol % or less, such as about 0.5 mol % or less of the total molar content of diol component B. In some embodiments, the additional hydroxyl-containing residue is selected from 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,4-pentanediol, 3-methyl-2,4-pentanediol, trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-diethyl-1,3-propanediol, 1,3-hexanediol, 1,4-di(hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(3-hydroxyethoxyphenyl)propane, and 2,2-bis(4-hydroxypropoxyphenyl)propane.
[0016] Dicarboxylic acid component A may further comprise one or more additional diacid residues. In some embodiments, the additional diacid residues are selected from isophthalic acid, naphthalenedicarboxylic acid, cyclohexanedicarboxylic acid, cyclohexanediacetic acid, 2,5-furandicarboxylic acid, succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, and combinations thereof.
[0017] The present disclosure also provides a method for preparing a copolyester, the method comprising subjecting terephthalic acid or its ester-forming derivative, 2,4-furandicarboxylic acid residue or its ester-forming derivative, and C2-C22 alkanediol to polycondensation conditions, and subjecting the polycondensation reaction to solid-state polymerization, wherein the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.1-10 mol % based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative. In some embodiments, the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.5-5 mol %, for example 1-3 mol %, based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative. In some embodiments, the C2-C22 alkanediol is selected from monoethylene glycol, propylene glycol, and butylene glycol.
[0018] The present disclosure also provides an article comprising a copolyester comprising a dicarboxylic acid component A comprising terephthalic acid residues or ester-forming derivatives thereof or mixtures thereof and 2,4-furandicarboxylic acid residues or ester-forming derivatives thereof or mixtures thereof, and a diol component B comprising an alkanediol residue having 2 to 22 carbon atoms, wherein the dicarboxylic acid component A has a total molar content and the 2,4-furandicarboxylic acid residues or ester-forming derivatives thereof are present in an amount of 0.1 to 10 mol % relative to the total molar content of the dicarboxylic acid component A. In some embodiments, the article further comprises one or more additional polymers. In some embodiments, the copolyester is layered adjacent to the additional polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Detailed Description The present invention discloses an innovative PET-based copolyester composition with advantageous properties and its preparation by polycondensation and solid-state polymerization of terephthalic acid and monoethylene glycol in the presence of 2,4-FDCA, preferably obtained by a fermentation process of bio-based feedstocks, and its application as copolymers with enhanced crystallization rate control, barrier properties, and high renewable content suitable for the manufacture of articles such as films, containers, and bottles.
[0020] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, a reference to a "carboxylic acid" includes a plurality of such carboxylic acids, a reference to a "diol" includes a reference to one or more diols, and so forth.
[0021] As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," "contains," "containing," or any other variations thereof, are intended to cover a non-exclusive inclusion. A composition, mixture, process, method, article, or device that contains a list of elements is not necessarily limited to only those elements and may include other elements not expressly listed or inherent to such composition, mixture, process, method, article, or device. Further, unless expressly indicated otherwise, "or" refers to an inclusive "or" and not an exclusive "or."
[0022] In this disclosure, the terms "bio-based" or "bio-" refer to a compound that is derived from biogenic materials and thus contains renewable carbon, where biogenic carbon is 14 Indicates traceability through C isotope measurement. "Biobased" can also be referred to as "renewable," "biosourced," "naturally derived," "plant-derived" or "plant-" or "derived from natural sources."
[0023] The term "copolyester" as used herein refers to a synthetic polymer prepared by the reaction of one or more di- or polyfunctional hydroxyl compounds with one or more di- or polyfunctional aliphatic carboxylic acids and one or more di- or polyfunctional aromatic carboxylic acids.
[0024] As used herein, the term "polyester" is intended to include "copolyesters."
[0025] The term "residue" as used herein means any organic structure that is incorporated into a polymer by a catalytic and / or enzymatic polycondensation reaction from the corresponding monomer.
[0026] In addition to the innovative copolyester, the present invention also claims advantageous applications of the innovative copolyester. Contrary to the prior art, 2,4-PETF exhibits enhanced crystallization rate control, better relative gas barrier properties against CO2 and O2, and improved resistance to oxidation, as compared to isophthalic acid and other diacids known in the art. 14 It exhibits a high renewable content as evidenced by C measurements. Thus, one skilled in the art could explore 2,4-PETF in technology to improve the shelf life of PET bottles, reduce the need for additives during polymerization, improve clarity, reduce haze, allow for thinner bottle walls, and essentially have more reliable performance over time.
[0027] Apart from the preferred use of 2,4-FDCA as a comonomer to modify PET resins, this comonomer is also used to modify the properties of other polyesters derived from the combination of aromatic and aliphatic diacids and diols to produce poly(alkylene terephthalates), such as PBT and PPT.
[0028] In some aspects, the present disclosure provides a copolyester comprising a dicarboxylic acid component A comprising terephthalic acid residues or ester-forming derivatives thereof or mixtures thereof and 2,4-furandicarboxylic acid residues or ester-forming derivatives thereof or mixtures thereof, and a diol component B comprising an alkanediol residue having 2 to 22 carbon atoms, wherein the dicarboxylic acid component A has a total molar content and the 2,4-furandicarboxylic acid residues or ester-forming derivatives thereof are present in an amount of 0.1 to 10 mol % relative to the total molar content of the dicarboxylic acid component A.
[0029] In some embodiments, at least one of the components of the copolyester is of renewable origin, i.e., according to ASTM 6866. 14 The copolyesters described herein are produced from renewable feedstocks, such as agricultural feedstocks, agricultural wastes, organic waste products, biomass, CO2, CO and microorganisms, that have biogenic carbon detectable by C measurements. In some embodiments, the copolyesters described herein have a lower carbon content as measured by ASTM D6866 when compared to comparable copolyesters that contain isophthalic acid instead of 2,4-furandicarboxylic acid. 12 For C 14 It has a high proportion of C. The component of renewable origin may be one or more of 2,4-FDCA, an alkanediol, and one or more other components.
[0030] The intrinsic viscosity of the copolymer can affect the ability to process and prepare container preforms and containers with sufficient mechanical integrity and performance. In some embodiments of the present invention, the copolyesters exhibit an intrinsic viscosity (IV) of 0.5 dL / g to 1.2 dL / g. IV properties are typically measured in a 0.5 wt% solution of 60 / 40 phenol / 1,1,2,2-tetrachloroethane at 30°C according to ASTM D4603-96. In some embodiments, the copolyesters have an intrinsic viscosity (IV) of 0.2 dL / g to 1.5 dL / g, e.g., 0.5 dL / g to 1.2 dL / g or 0.7 dL / g to 1 dL / g, measured in a 0.5 wt% solution of 60 / 40 phenol / 1,1,2,2-tetrachloroethane at 30°C according to ASTM D4603-96.
[0031] In another embodiment, the copolyesters described herein have a molecular weight, defined in the art as the resultant average polymer molecular weight, or simply Mn, in the range of about 10 kDa to about 400 kDa, as measured by methods known in the prior art.
[0032] Due to the asymmetry of 2,4-FDCA, it is surprising that 2,4-FDCA plays a role in the crystallization of polyesters, and even small amounts of 2,4-FDCA can effectively control the crystallization rate while simultaneously enhancing the barrier properties. In some embodiments, the copolyesters described herein have slower crystallization rates compared to comparable copolyesters that contain isophthalic acid instead of 2,4-furandicarboxylic acid.
[0033] In some embodiments, the copolyesters described herein have an increased gas barrier property to CO2 and O2 of at least 15%, e.g., at least 10% or at least 8%, as measured by ASTM D1927-20, compared to a comparable copolyester comprising isophthalic acid instead of 2,4-furandicarboxylic acid.
[0034] Dicarboxylic acid component A Terephthalic acid residue The diacid compound contains terephthalate units. Typically, the terephthalate compounds used to make BioPET are terephthalic acid or dimethyl terephthalate. Terephthalic acid with a purity of greater than 99% is typically sold as "pure terephthalic acid", or "purified terephthalic acid" or simply "PTA" and is usually preferred to achieve polymers with advantageous levels of transparency.
[0035] In some embodiments, the dicarboxylic acid component A has a total molar content and the terephthalic acid residues are present in an amount of from about 90 mol % to about 99.9 mol %, e.g., from 95 mol % to about 99.9 mol %, or from 96.5 mol % to about 99.9 mol %, based on the total molar content of the dicarboxylic acid component A.
[0036] 2,4-Furandicarboxylic acid residue The 2,4-furandicarboxylic acid residues of the polyester of the present invention include 2,4-furandicarboxylic acid (2,4-FDCA), its ester-forming derivatives, such as 2,4 dimethyl furanoate, and mixtures of 2,4-FDCA, its ester-forming derivatives, and / or one or more aromatic dicarboxylic acids. In some embodiments, 2,4-FDCA or its ester-forming derivatives can be used individually. In some embodiments, mixtures of two or more aromatic dicarboxylic acids, including 2,4-FDCA or its ester-forming derivatives, such as 2,4 dimethyl furanoate, can be used.
[0037] In some embodiments, 2,4-furandicarboxylic acid or an ester-forming derivative thereof is incorporated into the polyester in a proportion of 1 to 70 mol %, preferably 20 to 60 mol %, and more preferably 30 to 50 mol %, based on the total molar content of the dicarboxylic acids.
[0038] 2,4-FDCA is a new furan isomer that can be synthesized from renewable carbon feedstocks with essentially low environmental impact. The optional use of renewable materials to produce 2,4-FDCA is a feature that allows the copolymers of the present invention to contain different levels of bio-based carbon, typically as assessed according to ASTM D6866. Furthermore, this process can make the production cost of this new isomer comparable to that of terephthalic acid, thus favoring the production of the copolyesters described herein.
[0039] In some aspects, the renewable carbon feedstock may be selected from sugars, glycerol, alcohols, organic acids, alkanes, fatty acids, lignocellulose, proteins, carbon dioxide, and carbon monoxide. The renewable carbon feedstock may be waste streams and agricultural feedstocks, such as, but not limited to, first generation sugars, second generation sugars, such as sugarcane and sugar beet, wheat, corn, or soybeans. In one aspect, the carbon feedstock is a sugar. In one aspect, the sugar is a monosaccharide. In one aspect, the sugar is a polysaccharide. In one aspect, the sugar is glucose or an oligomer of glucose. In one aspect, the oligomer of glucose is selected from fructose, sucrose, starch, cellobiose, maltose, lactose, and cellulose. In one aspect, the sugar is a pentose. In one aspect, the sugar is a hexose. In some aspects, the renewable carbon source (i.e., the feedstock) comprises one or more pentoses and / or one or more hexoses. In some aspects, the feedstock comprises one or more of xylose, glucose, arabinose, galactose, maltose, fructose, mannose, sucrose, and / or combinations thereof. In some aspects, the feedstock comprises one or more of xylose and / or glucose. In some aspects, the feedstock comprises one or more of arabinose, galactose, maltose, fructose, mannose, sucrose, and / or combinations thereof.
[0040] In another embodiment, 2,4-FDCA is produced by a catalytic route comprising several synthetic steps as described in Org.Proc.Res.Dev. 2003, 7, 1, 74-81, Anti-Infective Agents, 2012, 10, 55-71, and ACS Sustainable Chem. Eng. 2016, 4, 3, 1707-1714.
[0041] In another embodiment, 2,4-FDCA is enzymatically produced to obtain bio-based 2,4-FDCA, for example, as described in US Patent Application Publication No. 2020 / 0277639, the entire contents of which are incorporated herein by reference. In some embodiments, the method for producing 2,4-FDCA includes culturing a recombinant microorganism in a medium containing a feedstock providing a carbon feedstock until 2,4-FDCA is produced. In some embodiments, the method for producing 2,4-FDCA includes culturing a recombinant microorganism in a medium containing a feedstock providing a carbon feedstock until 2,4 FDME is further oxidized to 2,4 FDCA by procedures known to those skilled in the art. The optional utilization of renewable materials to produce 2,4 FDCA is a feature that allows the copolymers of the present invention to contain different levels of bio-based carbon, typically as assessed according to ASTM D6866. The bio-based content can be further expanded by using bio-based monoethylene glycol and other bio-based glycols as other comonomers, such as isosorbide, mannitol, etc.
[0042] In another embodiment, 2,4-FDCA or a derivative thereof is obtained from bio-based or petrochemical feedstocks and catalytic routes, e.g., those described in U.S. Pat. No. 9,284,290, U.S. Pat. No. 8,455,668, and Green Chem., 2014, 16, 1957-1966, ACS Sustainable Chem. Eng. 2016, 4, 3, 1707-1714, which are incorporated by reference in their entireties. In some embodiments, a method for synthesizing 2,4-FDCA by a disproportionation pathway includes the steps of: (a) oxidizing a furfural compound in the presence of a catalyst and an alkaline solution to obtain a bio-based furoate salt, the catalyst being selected from the group consisting of Au / TiO2, Au / C, Au / ZnO, Au / Fe2O3 or other Au catalysts; (b) heating the furoate salt with stirring in the presence of a metal-based catalyst to prepare a reaction mixture, and cooling the reaction mixture to room temperature; (c) recovering furans from the reaction mixture obtained in item (b) to obtain a mixture of 2,4-FDCA and 2,5-FDCA; and (d) subjecting the mixture obtained in item (c) to extraction or other separation methods to recover and purify 2,4-FDCA.
[0043] In some embodiments, the 2,4-furandicarboxylic acid residue or an ester forming derivative thereof is present in an amount of 0.1 to 10 mol %, such as 0.5 to 5 mol %, or 1 to 3 mol %, based on the total molar content of the dicarboxylic acid component A.
[0044] Additional aromatic dicarboxylic acid residues In some embodiments, the dicarboxylic acid component A may further comprise one or more additional dicarboxylic acid ("diacid") residues. Reference to a diacid residue as used herein includes carboxylic acid and its corresponding ester-forming derivatives. Thus, reference to a diacid residue herein should be understood to include its corresponding ester-forming derivatives.
[0045] Diacids suitable for use in the copolyesters of the invention include those having from 2 to 22 carbon atoms, for example, from 4 to 16 carbon atoms or from 4 to 10 carbon atoms. However, diacids suitable for use in the copolyesters of the invention may have a greater number of carbon atoms, for example, up to 30 carbon atoms, such as from 2 to 30 carbon atoms, from 4 to 30 carbon atoms, from 10 to 30 carbon atoms, or from 16 to 30 carbon atoms.
[0046] Suitable diacid residues may be linear or branched aliphatic carboxylic acid compounds. Examples of suitable carboxylic acids include, but are not limited to, oxalic acid, malonic acid, succinic acid, glutaric acid, 2-methylglutaric acid, 3-methylglutaric acid, α-ketoglutaric acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, brassylic acid, fumaric acid, 2,2-dimethylglutaric acid, suberic acid, diglycolic acid, oxaloacetic acid, glutamic acid, aspartic acid, itaconic acid, maleic acid, octadecanedioic acid, its ester-forming derivatives, and mixtures thereof.
[0047] In some embodiments, the additional diacid residues are selected from isophthalic acid, naphthalenedicarboxylic acid, cyclohexanedicarboxylic acid, cyclohexanediacetic acid, 2,5-furandicarboxylic acid, succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, and combinations thereof.
[0048] In some embodiments, the additional diacid residues are present in an amount of 5 mol % or less, based on the total molar content of dicarboxylic acid component A. For example, the additional diacid residues can be present in an amount of about 3.5 mol % or less, about 2.5 mol % or less, about 1 mol % or less, or about 0.5 mol % or less. In some embodiments, the additional diacid is present in an amount of about 0.5 mol % to about 5 mol %, or about 1 mol % to about 4 mol %.
[0049] Diol component B In some embodiments, the diol component B comprises at least one alkane diol residue or alkene diol residue. In some embodiments, the at least one alkane diol residue is selected from a branched or straight chain alkane diol having 2 to 22 carbon atoms, for example, 2 to 12 carbon atoms, 4 to 6 carbon atoms, or a mixture of two or more thereof. In some embodiments, the at least one alkane diol residue is selected from a cycloalkane diol having 5 to 22 carbon atoms, for example, 5 to 10 carbon atoms, or a mixture of two or more thereof. In some embodiments, the at least one alkene diol residue is selected from a branched or straight chain alkane diol having 2 to 22 carbon atoms, for example, 2 to 12 carbon atoms, 4 to 6 carbon atoms, or a mixture of two or more thereof. In some embodiments, the at least one alkene diol residue is selected from a cycloalkene diol having 5 to 22 carbon atoms, for example, 5 to 10 carbon atoms, or a mixture of two or more thereof. In some embodiments, the at least one alkenediol is selected from cycloalkenediols having 5 to 22 carbon atoms, such as 5 to 10 carbon atoms, or a mixture of two or more thereof.
[0050] Examples of suitable alkanediol, cycloalkanediol, alkenediol, and / or cycloalkenediol residues include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1-5-pentanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2,2-dimethyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 2,2,4-trimethyl ... Examples of suitable alkanediols include, but are not limited to, 1,6-hexanediol, in particular ethylene glycol, 1,3-propanediol, 1,4-butanediol, and 2,2-dimethyl-1,3-propanediol (neopentyl glycol); cyclopentanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 2,5-bis(hydroxymethyl)furan, and 2,4-bis(hydroxymethyl)furan. Mixtures of various alkanediols and / or alkenediols can also be used.
[0051] In some embodiments, the alkanediol residues may include monoethylene glycol (MEG) residues, propylene glycol residues, and / or butylene glycol residues. In some embodiments, diol component B includes two or more of monoethylene glycol residues, propylene glycol residues, and butylene glycol residues.
[0052] In some embodiments, the diol component B is of bio-based origin.
[0053] In some embodiments, diol component B comprises at least 92.5 mol%, preferably 99 mol%, and even more preferably 100 mol% monoethylene glycol. Nevertheless, diethylene glycol moieties are often found inherently in the resulting copolyester chains, since they are produced as a condensation product between two monoethylene glycol units during the polymerization stage. Thus, diethylene glycol may be found in the resulting chains even if it is not deliberately added as a compound. The molar concentration of diethylene glycol units in the copolyester is preferably less than 3.5 mol%, more preferably less than 1 mol%, based on the total molar content of diol component B. Control of the production of diethylene glycol, including the selection of the right polymerization catalyst, including lithium acetate dehydrate, to reduce the amount of diethylene glycol produced at this stage, is taught in U.S. Pat. No. 3,830,759 A, which is incorporated herein by reference in its entirety.
[0054] In preferred embodiments, all or a majority of the MEG is derived from bio-based feedstocks that allow the copolyester compositions to contain different levels of bio-based carbon, typically as tested and measured according to ASTM D6866. BioMEG can be obtained from different routes, such as fermentation and hydrogenolysis and hydroformylation, as described in detail in U.S. Pat. No. 6,297,409 B, US 2008 / 0228014 A1, U.S. Pat. No. 4,496,781 B1, U.S. Pat. No. 4,396,781 B1, U.S. Pat. No. 4,321,414 A, U.S. Pat. No. 4,200,765 B1, U.S. Pat. No. 4,321,414 B1, U.S. Pat. No. 4,317,946 B1, EP 0 002 908 B1, U.S. Pat. No. 5,210,337 B1, U.S. Pat. No. 9,695,276, U.S. Pat. No. 2018 / 0355100 A1 and U.S. Pat. No. 9,926,247 B2, the disclosures of each of the foregoing are incorporated herein by reference in their entirety.
[0055] In some embodiments, diol component B is present in an amount of about 95-105 mol % based on acid component A. In some embodiments, diol component B is present in an amount of about 98-102 mol % based on acid component A. In some embodiments, diol component B is present in an amount of about 100 mol % based on acid component A.
[0056] Hydroxyl-Containing Additives In some embodiments, the disclosed copolyesters may also include less than 7.5 mol % based on diol component B, e.g., less than 5 mol % based on diol component B, less than 1 mol % based on diol component B, and less than 0.5 mol % based on diol component B of other hydroxyl-containing compounds. Such other hydroxyl-containing compounds may be added to control the properties of the copolyester and may not be inherently present in the copolyester composition with monoethylene glycol. These hydroxyl-containing compounds may include compounds known in the art, such as 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,4-pentanediol, 3-methyl-2,4-pentanediol, trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-diethyl-1,3-propanediol, 1,3-hexanediol, 1,4-di(hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(3-hydroxyethoxyphenyl)propane, and 2,2-bis(4-hydroxypropoxyphenyl)propane.
[0057] Compositions and Articles Applications of the copolyesters of the invention having improved properties include films, especially uniaxially and biaxially oriented films, multilayer films with other polymeric materials, blown films and articles, injection molded articles, extrusion coatings, extruded and coextruded fibers, blended composite fibers, nonwoven fibers, and the like.
[0058] In some embodiments, the copolyesters of the present invention can be used in multilayer films, coextrusions or blend composites with one or more other polymers to form compositions. In some embodiments, the polyesters of the present invention can be blended with polyolefins, aliphatic and semi-aromatic polyesters that may or may not be biodegradable, polyamides, polyurethanes, polycarbonates, polyurethanes, polyureas, polyacids, polymers obtained entirely from biobased sources, polyacids or other biodegradable polymers such as aliphatic-aromatic copolyesters with different structures, polyesters such as polylactic acid (PLA), modified natural polymers such as thermoplastic starch, or mixtures thereof. In some embodiments, it is preferred to blend the copolyesters of the present invention with one or more other biodegradable polymers such as aliphatic-aromatic copolyesters with different structures, polyesters such as polylactic acid (PLA), modified natural polymers such as thermoplastic starch.
[0059] In some embodiments, the compositions of the present invention may further comprise one or more additives to improve properties, including, but not limited to: (i) fillers to reduce cost and / or improve mechanical properties, e.g., talc, mica and other inorganic fillers, organic fillers, and fibers such as lignocellulosic fibers and biochar; (ii) nucleating agents to control tacking, and other conventional additives to polyesters known to those skilled in the art.
[0060] In some embodiments, the copolymers and / or compositions of the present invention, when properly processed, are particularly suitable for use in producing packaging articles such as containers, bottles, flasks, and / or vessels using methods including, but not limited to, injection molding and stretch blow molding.
[0061] In some embodiments, the copolyesters and compositions disclosed herein and articles thereof can be separated and recycled according to conventional methods and recycling operating conditions known to those skilled in the art. In some embodiments, packaging articles made with the copolyesters or compositions disclosed herein are mechanically recycled in the form of chips or granules. Thus, the resulting chips and granules are typically recycled by: 14 The resulting chips or granules may be reprocessed into the same or different PET-based packaging articles using processing techniques and conditions known to those skilled in the art. Reprocessing may be done with, but is not limited to, PET from chips and granules obtained by recycling petrochemical feedstocks or petrochemical PET, and PET from biogenic feedstocks.
[0062] method Due to its similar reactivity, 2,4-FDCA can be incorporated into PET formulations by polycondensation and solid-state polymerization methods known in the art. This step can be reproduced using either bio-based or petroleum-based 2,4-FDCA.
[0063] For example, in some embodiments, the copolyesters described herein can be produced by a process comprising subjecting terephthalic acid or its ester-forming derivative, 2,4-furandicarboxylic acid residue or its ester-forming derivative, and a C2-C22 alkanediol to polycondensation conditions, and subjecting the polycondensation reaction to solid-state polymerization, wherein the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.1-10 mol % based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative. In some embodiments, the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.5-5 mol %, for example 1-3 mol %, based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative. In some embodiments, the C2-C22 alkanediol is selected from monoethylene glycol, propylene glycol, and butylene glycol.
[0064] The properties of the copolymer resulting from this reaction, referred to herein as 2,4-PETF or simply the copolyesters of the invention, can be tailored by variation of the molar ratio of terephthalic acid:2,4-FDCA. In a preferred embodiment, the present disclosure includes copolyesters having a 2,4-FDCA ratio ranging from 0.1 to 10 mole % based on the total dicarboxylic acid component A content. EXAMPLES
[0065] Example 1 In vivo production of 2,4-FDCA from glucose by the recombinant microorganisms described in U.S. Patent Application Serial No. 16 / 806,728 was evaluated in triplicate in shake flask fermentations using a defined medium containing approximately 2.2 g / L KH2PO4, 9.4 g / L K2HPO4, 1.3 g / L (NH4)2SO4, 10 mg / L thiamine, 320 mg / L EDTA-NaOH, 2 mg / L CoCl2·6H2O, 10 mg / L MnSO4·H2O, 5 mg / L CuSO4·5H2O, 2 mg / L H3BO3, 2 mg / L Na2MoO4·2H2O, 54 mg / L ZnSO4·7H2O, 1 mg / L NiSO4·6H2O, 100 mg / L Fe(III) citrate, 100 mg / L CaCl2·2H2O, and 0.3 g / L MgSO4·H2O. The carbon source for 2,4-FDCA production was supplied by 10 g / L glucose, and sulfate nitrogen was used as the nitrogen source. Erlenmeyer flasks were inoculated with the recombinant strain to an initial optical density (OD600) of 0.1 and incubated at 37°C and 225 rpm for approximately 48 hours. High performance liquid chromatography (HPLC) analysis of the supernatant at 48 hours indicated 2,4-FDCA production of 14±2 mg / L. As used herein, the term "EDTA-NaOH" refers to the soluble salt of ethylenediaminetetraacetic acid (EDTA) and sodium hydroxide (NaOH).
[0066] Example 2 A non-limiting example of a procedure for preparing 2,4-FDCA was tested.
[0067] In this non-limiting example, the procedure for synthesizing 2,4-FDCA by the disproportionation route includes the following steps: (a) oxidizing furfural compounds in the presence of a catalyst and an alkaline solution to obtain a bio-based furoate salt, the catalyst being selected from the group consisting of Au / TiO2, Au / C, Au / ZnO, Au / Fe2O3, or other Au catalysts; (b) heating the furoate salt with stirring in the presence of a metal-based catalyst to prepare a reaction mixture, and cooling the reaction mixture to room temperature; (c) recovering furans from the reaction mixture obtained in item (b) to obtain a mixture of 2,4-FDCA and 2,5-FDCA; and (d) subjecting the mixture obtained in item (c) to extraction or other separation methods to recover and purify 2,4-FDCA. The procedure is described in more detail below.
[0068] A procedure for the preparation of furoic acid from furfural: Oxidation of furfural Furfural (3.00 g, 31.22 mmol) was dissolved in 40 ml of water. One equivalent (31.75 mmol; 1.02 equiv.) of base (NaOH) and 0.012 g of Au / TiO2 catalyst (ex-Strem-Autek; 1.2 wt.% Au, Au particle size 2-3 nm) were added to the furfural aqueous solution. A 100 ml reaction vessel (Buchi glasuster picoclave) was closed and overhead stirring was performed. The reaction mixture was subjected to oxygen pressure (303974.99 Pa O2). The reaction mixture was placed at 50 °C. After 1 h of reaction, the pressure dropped to about 1 atm and the reaction vessel was repressurized to 303974.99 Pa O2, followed by stirring overnight. After stirring overnight, the reaction was stopped and the catalyst was filtered off. The solvent (water) was removed under reduced pressure by rotary evaporator. The yield of sodium furoate was 94.9%.
[0069] The use of gold catalysts in the above reactions is often slightly more selective than other metal-based catalysts such as Pt or Pd, and in the circumstances used for this reaction, a heterogeneous catalyst combination operating under the same basic conditions required for the subsequent disproportionation reaction would be advantageous.
[0070] This reaction demonstrates the efficiency of obtaining furoate salts from furfural, which serve as input for the subsequent disproportionation reaction.
[0071] Process for the production of a mixture of 2,4-FDCA and 2,5-FDCA 6.00 g of K-furoate (39.95 mmol) and 2.20 g of Cdl2 (6.01 mmol) were thoroughly ground together and added to a three-necked flat flange reaction vessel. The mixture was then heated in a salt bath at 265 °C with stirring using a mechanical overhead stirrer under continuous (very slow) nitrogen flow. During the reaction, the furan formed was collected in a Dean-Stark trap and a CO2 / acetone ice bath (-78 °C) to obtain 1.35 g (95% of theoretical amount) of furan. After 4 hours, the reaction was stopped and cooled at room temperature for 1 hour. The black, hard solid thus obtained was dissolved in water (50 mL). The residual amount of water-insoluble black material was filtered off and the thick yellow filtrate was acidified (to pH: 1) with 12 N HCl. 2,5-FDCA was precipitated and filtered. 60.9% of theoretical amount of 2,5-FDCA was isolated. NMR analysis of the reaction mixture after filtering off the insoluble black material showed that K-furoate was over 90% converted and that a mixture of 2,4-FDCA and 2,5-FDCA was present in a ratio of 0.32:0.68. Based on this and the 60.9% of 2,5-FDCA isolated, it can be calculated that K-furoate was disproportionated to a mixture of furandicarboxylic acids in 89% of the theoretical yield.
[0072] Procedure for the purification of 2,4-furandicarboxylic acid (2,4-FDCA) The crude reaction mixture (2,4-FDCA, 2,5-FDCA, 2-furoic acid and Cdl2) was subjected to Soxhlet extraction with acetone for 8 hours. After cooling to room temperature, the acetone-insoluble white crystalline powder was analyzed by NMR, which showed no proton signals. The acetone-soluble portion was collected and the solvent was evaporated under reduced pressure by rotary evaporator. NMR analysis showed the presence of 2,4-FDCA, 2,5-FDCA, and 2-furoic acid in the crude mixture. The mixture was then vigorously stirred with chloroform at room temperature for 10 minutes and filtered. This process was repeated until 2-furoic acid was completely removed from the mixture. The product was then dried in a vacuum oven at 40 °C for 12 hours. Due to the relatively high solubility difference of 2,4-FDCA in acetone at room temperature, the same technique (previously adapted with chloroform) was repeated with acetone to separate 2,4-FDCA from 2,5-FDCA. The acetone-soluble portions were separated in this manner, combined, and evaporated under reduced pressure using a rotary evaporator to obtain 2,4-FDCA, which was not 100% qualitatively but had a purity of 85% or more. We are currently investigating a more accurate method for obtaining a compound with 100% purity of 2,4-FDCA.
[0073] Use of the process described herein allows for yields of 2,4-FDCA of at least 7% by weight, preferably at least 15-20% by weight, more preferably at least 32% by weight (the remaining fraction of the product is essentially 2,5-FDCA). 2,4-FDCA is produced from cheap and renewable raw materials, such as furfural, by a simple two-step process that does not produce harmful, toxic or undesirable by-products (although the main by-product furan has very interesting applications in practice).
[0074] Example 3 A non-limiting example of a procedure for preparing 2,4-FDCA was tested.
[0075] In a 250 mL jacketed glass reactor, dihydroxyacetone (10.0 g, 0.11 mol, 1 equiv.) was dissolved in deionized water (100 mL). The solution was cooled to 0° C. and Ambersep-900 basic ion exchange resin (27.8 g) was added. The mixture was then stirred at 0° C. for 24 h. After filtration to remove the resin, the product was lyophilized.
[0076] The product was redissolved in DMSO (50 mL) in a 100 mL round bottom flask to which Amberlyst-15 acidic ion exchange resin (5.0 g) was added. A Dean-Stark trap was fitted to collect the water produced during dehydration. The mixture was stirred at 110° C. for 5 h, then cooled to room temperature and filtered. The filtrate was concentrated under reduced pressure to remove most of the DMSO, keeping the temperature below 50° C. The product was then extracted by dichloromethane / NaHCO3 (1M) partition. The organic layer was dried over anhydrous sodium sulfate and the solvent was evaporated under reduced pressure. The final product (mixture of 4- and 5-HMF) was obtained as a brown viscous mass.
[0077] In a 250 mL round bottom flask, 4-HMF was dissolved in aqueous sodium hydroxide (9.2 g NaOH / 100 mL deionized water). The mixture was cooled to 0° C. and potassium permanganate (3.4 g, 22 mmol, 34 equiv.) was added. The solution was then stirred at 0° C. for 15 min. The manganese oxide precipitate was filtered off and concentrated HCl solution was carefully added to the filtrate to bring the pH to 1, keeping the temperature below 5° C. The resulting mixture was extracted with diethyl ether (×2). The organic layer was dried over anhydrous sodium sulfate and concentrated under reduced pressure. The product was obtained as a yellow powder.
[0078] Example 4 Non-limiting examples of procedures for preparing the inventive copolyesters of the present disclosure were tested.
[0079] In a typical reaction, novel copolyesters were prepared with various amounts (mol%) of 2,4-FDCA and terephthalic acid (molar ratio of diol / diacid=1.6) in excess monoethylene glycol according to the scheme shown in Figure 1. The catalyst (1% w / w of Sb2O3) was placed in a two-neck round-bottom flask. Under argon protection, the system was heated to 180°C to initiate the transesterification. This stage was expected to be completed within 3 hours. The pressure was slowly reduced to 0.04 mbar for the melt polycondensation stage. Then the reaction temperature was increased to 250°C and this stage continued for 4 hours. Finally, the reaction pressure was returned to normal atmospheric pressure and the copolyester was obtained as a grey powder after washing with methanol and drying at 90°C. Copolyesters with PTA / 2,4-FDCA molar ratios of 98 / 2 and 94 / 6 were prepared as copolyesters of the present invention, and comparative examples were prepared with 100 / (i.e., without 2,4-FDCA).
[0080] TIFF2024504461000001.tif16145Figure 1: Scheme for the preparation of the inventive copolyesters disclosed herein.
[0081] Example 5 Non-limiting examples of the chemical properties of the inventive copolyesters of the present disclosure have been tested.
[0082] The chemical structure of the product was confirmed by NMR spectroscopy at 300 MHz Bruker NMR spectrometer. 1 H nuclear magnetic resonance ( 1 The final molar composition of each copolymer was determined by 1 H NMR in deuterated chloroform (CDCl3) with the addition of a few drops of trifluoroacetic acid (TFA). 1 The H NMR spectrum was calculated by comparing the integrals of the furan signals at 7.7 and 8.3 ppm with the aromatic signal at 8.2 ppm. The resonance signals confirmed that the novel copolyester was successfully prepared by polycondensation of terephthalic acid and monoethylene glycol in the presence of 2,4-FDCA. The synthesis was also confirmed by FTIR, where the furan ring-related peaks at 3140 cm -1 and 1590 cm -1ν(=CH) and ν(C=C) of the ester bond formed during polymerization, and ν(C=O) of the ester bond formed during polymerization. -1 This was also confirmed by the presence of
[0083] Table 1: Chemical properties of the copolyesters of the present invention and comparative examples TIFF2024504461000002.tif61146
[0084] Example 6 Non-limiting examples of the thermal and optical properties of the inventive copolyesters of the present disclosure were tested.
[0085] The melting behavior of the polyesters of the present invention was recorded by differential scanning calorimetry (DSC TA Instruments Q2000). The samples were heated from -80°C to 350°C at a rate of 10°C / min. Thermogravimetric analysis (TGA) was carried out using a TA Instruments TGA550. The samples were heated from 25°C to 700°C at 10°C / min under nitrogen flow. Optical properties such as transparency were investigated by spectroscopy in the ultraviolet and visible wavelength range (300-800 nm) at room temperature for thick film samples. Data from thermal and optical properties obtained for the copolyesters of the present invention and comparative examples are shown in Table 2.
[0086] Table 2: Thermal and optical properties of the copolyesters of the present invention and comparative examples TIFF2024504461000003.tif76146
[0087] From the DSC results, the incorporation of 2,4-FDCA units into the PET structure appears to decrease the melting temperature (Tm) of the polyester. Even though the introduction of 1.3% 2,4-FDCA does not result in a significant change in Tm, the presence of 3.3% 2,4-FDCA results in a decrease in Tm of about 14°C. These results clearly demonstrate the effect of 2,4-FDCA on the decrease of the crystallinity of PET.
[0088] In terms of thermal stability, considering Td5%, 2,4-FDCA is inherently less stable compared to PTA, so the incorporation of 2,4-FDCA into the PET structure appears to dramatically decrease the thermal stability of the polymer, as reported in the art. All polyesters are stable in the processing windows typically used in the art for the processing and use of this type of polyester, indicating that the copolyesters of the present invention can be advantageously used in the manufacture of articles. Furthermore, Td max The thermal stability as determined by the method of the present invention is astonishingly high at 426° C.
[0089] With respect to transparency, the copolyesters of the present invention exhibited less permeability when analyzed versus the comparative examples, which represents an advantageous feature of the copolyesters of the present invention since this property can be correlated with desirable properties of the article produced.
[0090] Example 7 Non-limiting examples of the barrier properties of the inventive copolyesters of the present disclosure were tested.
[0091] The gas barrier properties were tested by Ox-Tran and Labthink VAC-V2 gas permeability tester at 30°C, 50% relative humidity, and 99.99% O2 and CO2 purity. For this test, films with a thickness of about 120 μm were prepared by hot pressing. All reported permeation data were the average of four or more measurements. The results are shown in Table 3 as relative barrier improvement factors (BIFs). p ) are indicated.
[0092] Table 3: Gas barrier properties of the copolyester of the present invention and comparative examples TIFF2024504461000004.tif31146
[0093] It has surprisingly been found that the incorporation of 2,4-FDCA units into the PET structure results in copolymers with better O2 and CO2 gas barrier, which can be advantageously explored to produce articles and containers with improved performance compared to the art.
Claims
1. Terephthalic acid residues or ester-forming derivatives thereof, or mixtures thereof, and 2,4-Furandicarboxylic acid residue or its ester derivative, or a mixture thereof a dicarboxylic acid component A comprising Diol component B, which contains an alkanediol residue having 2 to 22 carbon atoms A copolyester comprising: Dicarboxylic acid component A has a total molar content of the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.1 to 10 mol % based on the total molar content of the dicarboxylic acid component A; Copolyester.
2. (a) the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.5 to 5 mol % based on the total molar content of the dicarboxylic acid component A, and optionally the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 1 to 3 mol % based on the total molar content of the dicarboxylic acid component A, or optionally the alkanediol residue is a branched or linear alkanediol having 4 to 6 carbon atoms; (b) the alkanediol residue is a branched or straight-chain alkanediol having 2 to 12 carbon atoms; (c) the alkanediol residue is a cycloalkanediol having 5 to 10 carbon atoms; (d) the alkanediol residue is a cycloalkenediol having 5 to 10 carbon atoms; (e) the alkanediol residue comprises a monoethylene glycol residue; (f) the alkanediol residues include propylene glycol residues; or (g) the alkanediol residue comprises a butylene glycol residue; 2. The copolyester of claim 1.
3. diol component B has a total molar content, and monoethylene glycol is present in an amount of 92.5 mol % or more, based on the total molar content of diol component B; or diol component B has a total molar content, and monoethylene glycol is present in an amount of 95 mole % or more based on the total molar content of diol component B; 3. The copolyester of claim 2.
4. diol component B has a total molar content, and monoethylene glycol is present in an amount of 99 mol % or greater, based on the total molar content of diol component B; or diol component B consists essentially of monoethylene glycol; or Diol component B contains two or more of monoethylene glycol residues, propylene glycol residues, and butylene glycol residues; 3. The copolyester of claim 2.
5. 2. The copolyester of claim 1, wherein diol component B further comprises additional hydroxyl-containing residues.
6. 6. The copolyester of claim 5, wherein diol component B has a total molar content of 1 to 50% by weight, and the additional hydroxyl-containing residues are present in an amount up to about 7.5 mole percent of the total molar content of diol component B.
7. the additional hydroxyl-containing residues are present in an amount of about 1 mole % or less of the total molar content of diol component B; or the additional hydroxyl-containing residues are present in an amount of about 0.5 mole % or less of the total molar content of diol component B; The copolyester of claim 6.
8. 6. The copolyester of claim 5, wherein the additional hydroxyl-containing residue is selected from 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,4-pentanediol, 3-methyl-2,4-pentanediol, trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,2-diethyl-1,3-propanediol, 1,3-hexanediol, 1,4-di(hydroxyethoxy)benzene, 2,2-bis(4-hydroxycyclohexyl)propane, 2,4-dihydroxy-1,1,3,3-tetramethylcyclobutane, 2,2-bis(3-hydroxyethoxyphenyl)propane, and 2,2-bis(4-hydroxypropoxyphenyl)propane.
9. (a) the alkanediol residues are of biobased origin; (b) dicarboxylic acid component A further comprises one or more additional diacid residues, optionally the additional diacid residues are selected from isophthalic acid, naphthalenedicarboxylic acid, cyclohexanedicarboxylic acid, cyclohexanediacetic acid, 2,5-furandicarboxylic acid, succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, and combinations thereof; (c) have a slower crystallization rate compared to an equivalent copolyester containing isophthalic acid instead of 2,4-furandicarboxylic acid; (d) having at least 10% increased gas barrier properties to CO2 and O2 as measured by ASTM D1927-20 compared to an equivalent copolyester containing isophthalic acid instead of 2,4-furandicarboxylic acid; (e) having a higher ratio of 14 C to 12 C as measured by ASTM D6866 when compared to a comparable copolyester containing isophthalic acid instead of 2,4-furandicarboxylic acid; (f) having an intrinsic viscosity (IV) of 0.5 dL / g to 1.2 dL / g, measured in a 0.5 weight percent solution of 60 / 40 phenol / 1,1,2,2-tetrachloroethane at 30° C. according to ASTM D4603-96; or (g) terephthalic acid residues are present in an amount of 96.5 mol % to about 99.9 mol %, based on the total molar content of dicarboxylic acid component A; 2. The copolyester of claim 1.
10. subjecting terephthalic acid or an ester-forming derivative thereof, a 2,4-furandicarboxylic acid residue or an ester-forming derivative thereof, and a C2 to C22 alkanediol to polycondensation conditions; and subjecting the polycondensation reaction to solid-state polymerization Including, wherein the 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.1 to 10 mol % based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative; A process for preparing a copolyester.
11. The 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 0.5 to 5 mol %, based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative; or The 2,4-furandicarboxylic acid residue or its ester-forming derivative is present in an amount of 1 to 3 mol %, based on the total molar content of terephthalic acid or its ester-forming derivative and 2,4-furandicarboxylic acid residue or its ester-forming derivative; or The C2-C22 alkanediol is selected from monoethylene glycol, propylene glycol, and butylene glycol; or The C2-C22 alkanediol is monoethylene glycol; 11. The method of claim 10.
12. 13. An article comprising the copolyester of claim 1.
13. 13. The article of claim 12, further comprising one or more additional polymers.
14. 14. The article of claim 13, wherein the copolyester of claim 1 is layered adjacent to an additional polymer.